2014
DOI: 10.1080/03602559.2014.935422
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characterization of Polyhydroxyalkanoates and Poly(lactic acid) Blends Obtained by Injection Molding

Abstract: In this work we present the thermal characterization of the full scope of polyhydroxyalcanoate and poly(lactic acid) blends obtain by injection molding. Blends of polyhydroxyalcanoate and poly(lactic acid) (PHA/PLA) were prepared in different compositions ranging from 0-100% in steps of 10%. The blends were injection molded and then characterized by differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and wide angle X-ray diffraction (WAXD). The increment of PHA fraction increased the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…, the miscibility is low (but not zero). Loureiro et al . observed a similar decrease in T g upon PHA additions to PLA.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…, the miscibility is low (but not zero). Loureiro et al . observed a similar decrease in T g upon PHA additions to PLA.…”
Section: Resultsmentioning
confidence: 62%
“…For PLA/PHA specimens, the first glass transition ( T g1 ) measured at around 0 °C corresponds to that of PHA and the second transition ( T g2 ) at around 55 °C corresponds to that of PLA . T g of PLA and PHA can depend on processing conditions, thermal history, and the extent of crystallization .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was clearly observed that T g of the PLA phase in the blend fibers shifted to a lower temperatures (52–57 °C) than that of neat PLA. A possible explanation for this might be that the molecular chain segments of the P3HB4HB amorphous phase with larger activity accelerated the unfreezing of molecular chain segments of the PLA amorphous phase at lower temperatures, so that T g of the PLA phase in the blend fibers exhibited a decreasing trend with the addition of P3HB4HB …”
Section: Resultsmentioning
confidence: 99%
“…The degrees of crystallinity (X c,fiber ) of neat P3HB4HB, PLA, and the P3HB4HB/PLA blend fibers, were calculated from the enthalpy of fusion according to the following eq. : Xnormalc,fiber=HmHnormalm,normalP3HB4HB100%WnormalP3HB4HB+Hnormalm,PLA100%WPLA×100%, where ∆ H m is the enthalpy of fusion of the blend fibers, and Hnormalm,normalP3HB4HB100% and Hnormalm,PLA100% are the theoretical enthalpies of fusion for 100% crystalline P3HB4HB and PLA, respectively. W P3HB4HB and W PLA are the weight fractions of P3HB4HB and PLA in the blend fibers, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation